Study on the path of Xi Jinping's ecological view for the high quality development of islands. Issue 1 (24th December 2021) - Zhang, Kuncheng; Tian, Shi-Zheng; Yang, Benshuo; Guo, Xin-Chang; Zhang, Yi-Fang
Abstract : Purpose: The island areas, in particular, are characterized by a more fragile ecological carrying capacity and higher value of resources and environment, which requires us to take Xi Jinping's green ecological development view as the theoretical basis and adhere to the high-quality development path of gradual development and ecological environment priority. Taking Shengsi and Daishan counties as examples, on the basis of their high-quality development evaluation and identification of the main influencing factors, this study explores the specific path of Xi Jinping's ecological development view in the high-quality development of typical island counties in China. Design/methodology/approach: This paper applies the interpretative structural model to construct an evaluation index system for the high-quality development of the island. In determining the factor weights of the index layer, the AHP hierarchical analysis method was combined with the Delphi method to increase the objectivity of the assignment process as much as possible. This study used the technique for order of preference by similarity to ideal solution to calculate island high quality development index. To measure the main obstacle factors, the index factor contribution rate, the index factor deviation, and the index factor obstacle degree were applied in this research. Findings: The study is supported by Guangxi Key Laboratory of Marine Environmental Science, Guangxi Academy of Sciences (GXKLHY21-04), Special Funds for Fundamental Scientific Research Operation of Central Universities (202113011), Shandong Provincial Social Science Planning Research Youth Project (21DSHJ2) and Tianjin Philosophy and Social Science Planning Project of China (No. TJKS20XSX-015). Originality/value: The connotation and extension of Xi Jinping's view of ecological development should be continuously studied in depth and enriched, with green development as the core idea to guide the correct direction of the high-quality development of the island. In this paper, it is suggested that researchers are supposed to focus on these problems, such as the changes of sea water quality, the reduction of urban greening, the continuous negative growth of population in island areas, the decline of forestry added value and air quality protection, so as to ensure the sustainable high-quality development of example islands.